Creative Business Entrepreneurship: the Portuguese creative business incubators - Pinho, Luis Fé de (2012)
Biographical notes: Luis Manuel Fe de Pinho is a Coordinator Professor of Marketing and Entrepreneurship in the School of Management of the Polytechnic Institute of Santarem (Portugal) as well as an Associate Professor of Tourism Marketing at the University Lusiada of Lisbon. He has a PhD in Economics and Business from the University of Huelva (Spain) and an MBA in Management from the UNL/Wharton Business School. He is the author of the book Corporate Strategy: The case of the wine sector in Portugal. His research areas are Entrepreneurship, Corporate Strategy, Marketing and Tourism. He is a consultant in Corporate Strategy and Marketing Management